Hubungan Rutinitas Literasi Keagamaan dan Kecerdasan Emosional Dengan Perilaku Santri Di Pondok Pesantren Teknologi Riau - Alhidayah, Rizka (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to determine the relationship between religious literacy routines and emotional intelligence with the behavior of students at the Riau Technology Islamic Boarding School. This research is a field research with a quantitative approach. The sample in this study were students at the Riau Technology Islamic Boarding School as many as 129 students. Data collection techniques using questionnaires, tests and documentation. Data analysis techniques using simple linear regression and multiple linear regression. The results of this study indicate that religious literacy routines are significantly related to the behavior of students at the Riau Technology Islamic Boarding School. It is shown byR value0.673Andthe value of R squre (R2) which shows the coefficient of determination, is 0.453, with a contribution of 45.3%. Emotional intelligence is significantly related to the behavior of students at the Riau Islamic Boarding School. It is shown byR value0.681 and the value of R squre (R2) which shows the coefficient of determination, is equal to 0.463, with a contribution of 46.3%. Likewise, there is a significant relationship between religious literacy routines and emotional intelligence with the behavior of students at the Riau Technology Islamic Boarding School. This is indicated by the results of the value of Fcount > Ftable (56.483 > 3.07), then Ha is accepted and H0 is rejected. Likewise with the results of the analysis of the determination of the relationship between the independent variable (routine religious literacy and emotional intelligence) and the dependent variable (student behavior), where the value of r squre (R2) is 0.473, in the sense that the percentage of the relationship between routine religious literacy and emotional intelligence with the behavior of students is 47.3%.